IL-10-independent regulatory B-cell subsets and mechanisms of action. (20th May 2015) - Ray, Avijit; Wang, Luman; Dittel, Bonnie N.
Abstract : IL-10-independent regulatory B cells Abstract : Although classically B cells are known to play important roles in immune protection via humoral immunity, recently their regulatory mechanisms have been best appreciated in the context of autoimmunity. Several studies have identified different subsets of regulatory B cells that vary not only in their phenotype but also in their mechanism of action. Although the best-studied mechanism of B-cell immune regulation is IL-10 production, other IL-10-independent mechanisms have been proposed. These include maintenance of CD4 + Foxp3 + regulatory T cells; production of transforming growth factor-β, IL-35, IgM or adenosine or expression of PD-L1 (programmed death 1 ligand 1) or FasL (Fas ligand). Given that B-cell-targeted therapy is being increasingly used in the clinic, a complete understanding of the mechanisms whereby B cells regulate inflammation associated with specific diseases is required for designing safe and effective immunotherapies targeting B cells.